Food Security and Nutrition - UNCTAD (World Bank, Washington, DC, 2018)
This note provides guidance on how to ensure tan agricultural investment makes a positive contribution to local and national food security and nutrition. Investments can play a critical role by introducing technologies to increase productivity, by providing demonstration effects, by creating quality jobs, by catalyzing modernization of the sector, and by linking small-scale producers with global markets—all of which, in the right circumstances, contribute to food securityand nutrition. Yet, investments can have a negative impact and be detrimental to food security and nutrition, especially where investments reduce local access to land and water. The challenge for policymakers and investors is how to design policy and business models that maximize the positive benefits to food security and nutrition but minimize the associated risks.